The adventures of Ichabod and Mr. Toad [videorecording (DVD)] - Crosby, Bing, 1903-1977; Rathbone, Basil, 1892-1967; Irving, Washington, 1783-1859; Grahame, Kenneth, 1859-1932 (Disney DVD., 2014)
Hang on for a wild ride with the fun-loving Mr. J. Thaddeus Toad. When his passion for motorcars lands him in hot water, he must rely on his faithful friends to clear his name. Then, meet the infamous Ichabod Crane whose comic rivalry for the affections of the town beauty leads to a heart-pounding race with the legendary Headless Horseman.